Solute transporters in plant thylakoid membranes: Key players during photosynthesis and light stress - Spetea, Cornelia (Landes Bioscience, 2010)
Plants utilize sunlight to drive photosynthetic energy conversion in the chloroplast thylakoid membrane. Here are located four major photosynthetic complexes, about which we have great knowledge in terms of structure and function. However, much less we know about auxiliary proteins, such as transporters, ensuring an optimum function and turnover of these complexes. The most prominent thylakoid transporter is the proton-translocating ATP-synthase. Recently, four additional transporters have been identified in the thylakoid membrane of Arabidopsis thaliana, namely one copper-transporting P-ATPase, one chloride channel, one phosphate transporter, and one ATP/ADP carrier. Here, we review the current knowledge on the function and physiological role of these transporters during photosynthesis and light stress in plants. Subsequently, we make a survey on the outlook of thylakoid activities awaiting identification of responsible proteins. Such knowledge is necessary to understand the thylakoid network of transporters, and to design strategies for bioengineering crop plants in the future.